2014
DOI: 10.1159/000362157
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Occlusion of Azygos/Hemiazygos Vein in Patients with Systemic Venous Collateral Development after the Bidirectional Glenn Procedure

Abstract: Objectives: To elucidate the feasibility and treatment effects of transcatheter occlusion of the azygos/hemiazygos vein in patients with progressive cyanosis after performing the bidirectional Glenn procedure. Methods: From January 2007 to May 2011, transcatheter closure was performed on 9 patients (7 males and 2 females) aged 5-15 years (median 9 years). Results: A total of 7 azygos veins and 3 hemiazygos veins were occluded successfully. Coils were employed in 4 of the procedures, patent ductus arteriosus (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…McElhinney et al 3 reported study of 55patients with median age of 1.4 years with collateral channels after BDG and successful coil embolization and increase in SaO 2 of 16%.Lu M. et al 6 reported on cohort study of nine patients with progressive cyanosis after BDG and median age of 9 years with successful trans catheter occlusion of the azygos/hemiazygosvein. Total 3 hemiazygos veins and 7 azygos veins occluded.…”
Section: Discussionmentioning
confidence: 99%
“…McElhinney et al 3 reported study of 55patients with median age of 1.4 years with collateral channels after BDG and successful coil embolization and increase in SaO 2 of 16%.Lu M. et al 6 reported on cohort study of nine patients with progressive cyanosis after BDG and median age of 9 years with successful trans catheter occlusion of the azygos/hemiazygosvein. Total 3 hemiazygos veins and 7 azygos veins occluded.…”
Section: Discussionmentioning
confidence: 99%
“…Veno-venous collaterals frequently occur after partial cavo-pulmonary connection (PCPC) for surgical palliation of patients with functionally univentricular hearts (UVH) ( 1 ), with a reported incidence that varies from 17% to as high as 31% ( 2 ). Veno-venous collaterals decrease the arterial oxygen saturation in such patients and may worsen the outcome ( 3 ).…”
Section: Introductionmentioning
confidence: 99%